2019
DOI: 10.1002/ird.2322
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Irrigation Scheduling and Superabsorbent Polymer‐ Hydrogel Enhance Seed Yield, Water Productivity and Economics of Indian Mustard Under Semi‐Arid Ecologies

Abstract: Oilseed brassicas are extensively grown in the water‐stressed ecologies of India. Sufficient irrigation, deficit irrigation scheduling (DIS) with limited irrigation water and rainfed (no irrigation) conditions were assessed with and without the use of superabsorbent polymer‐hydrogel (SAP‐hydrogel) under a micro‐sprinkler irrigation system (MIS) for Indian mustard. Irrigation scheduling at an irrigation water/cumulative pan evaporation ratio (IW/CPE) of 0.8, 0.6 and 0.4, along with use of SAP‐hydrogel, produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Enhanced root development and plant growth regulation by improvement in water-retention capacity and cluster structures of soil through hydrogel are useful in achieving higher production ( Akelah, 2013 ). Similar results of yield advantage and higher nutrient uptake have been reported by ( Singh et al., 2017 ) in mustard, ( Rathore et al., 2019 ), in pearl millet, and by ( Dai et al., 2017 ) in sorghum.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Enhanced root development and plant growth regulation by improvement in water-retention capacity and cluster structures of soil through hydrogel are useful in achieving higher production ( Akelah, 2013 ). Similar results of yield advantage and higher nutrient uptake have been reported by ( Singh et al., 2017 ) in mustard, ( Rathore et al., 2019 ), in pearl millet, and by ( Dai et al., 2017 ) in sorghum.…”
Section: Discussionsupporting
confidence: 88%
“…The hydrogel application increases plant survival ( Woodhouse and Johnson 1991 ) and dry matter production and prolongs the stay-green quality ( Callaghan et al., 1988 ), particularly under moisture, constrained situations ( Yangyuoru et al., 2006 ). The enhanced nutrient availability through enhanced longevity of water availability and uptake improves plant growth and yield attributes in hydrogel amended plots ( Rathore et al., 2019 , Chen et al., 2003 ). In the present investigation, the hydrogel application enhances the seed yield of mustard by 15.6% over no hydrogel application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar was the trend with MWUE (Table 4 and Fig 1). Under arid and semi-arid conditions,Rathore et al (30) also reported higher WUE ofmustard crop. This was due to higher productivity of karonda based AFS and better prevailing market prices of the karonda fruits.…”
Section: Discussionmentioning
confidence: 92%